A conformational switch in collybistin determines the differentiation of inhibitory postsynapses. (31st July 2014) - Soykan, Tolga; Schneeberger, Daniela; Tria, Giancarlo; Buechner, Claudia; Bader, Nicole; Svergun, Dmitri; Tessmer, Ingrid; Poulopoulos, Alexandros; Papadopoulos, Theofilos; Varoqueaux, Frédérique; Schindelin, Hermann; Brose, Nils
Abstract The formation of neuronal synapses and the dynamic regulation of their efficacy depend on the assembly of the postsynaptic neurotransmitter receptor apparatus. Receptor recruitment to inhibitory GABAergic and glycinergic synapses is controlled by the scaffold protein gephyrin and the adaptor protein collybistin. We derived new insights into the structure of collybistin and used these to design biochemical, cell biological, and genetic analyses of collybistin function. Our data define a collybistin‐based protein interaction network that controls the gephyrin content of inhibitory postsynapses. Within this network, collybistin can adopt open/active and closed/inactive conformations to act as a switchable adaptor that links gephyrin to plasma membrane phosphoinositides. This function of collybistin is regulated by binding of the adhesion protein neuroligin‐2, which stabilizes the open/active conformation of collybistin at the postsynaptic plasma membrane by competing with an intramolecular interaction in collybistin that favors the closed/inactive conformation. By linking trans‐synaptic neuroligin‐dependent adhesion and phosphoinositide signaling with gephyrin recruitment, the collybistin‐based regulatory switch mechanism represents an integrating regulatory node in the formation and function of inhibitory postsynapses.